2010
DOI: 10.1177/0883073810363917
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Treatment for a Giant Infantile Brain Cavernoma

Abstract: A term infant with Crouzon syndrome underwent a computed tomography (CT) study to rule out the presence of hydrocephalus. Computed tomography revealed hydrocephalus, a large cerebrospinal fluid cyst in the posterior fossa and hypoplastic cerebellar hemispheres with a winged appearance, consisting of Dandy-Walker malformation (Figure 1). The patient underwent a cystoperitoneal shunt insertion to alleviate pressure, and a craniofacial reconstructive procedure was performed at a later time.Crouzon syndrome is a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…The seven compounds selected from our automated analysis and validated by our secondary screen include compounds from classes previously connected to CCM disease, as well as compounds without any previously described association with the disease (Supplementary Table 2, Supplementary Fig. 3B–H) 4750 .…”
Section: Resultsmentioning
confidence: 99%
“…The seven compounds selected from our automated analysis and validated by our secondary screen include compounds from classes previously connected to CCM disease, as well as compounds without any previously described association with the disease (Supplementary Table 2, Supplementary Fig. 3B–H) 4750 .…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Clinical experiences in treating infantile hemangioma in a recent study show that propranolol is more effective than corticosteroids, especially for severe and large hemangiomas. 9,19,20 All other treatments have their limits in cases of orbital and nasal hemangiomas, which may lead to severe cosmetic, functional, and psychologic impairments. Propranolol was the first choice because excisional surgery leaves scars and intralesional steroids have a high risk of nasal ulceration and ophthalmic artery occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate drugs, like the ␤-adrenergic receptor blocker, propranolol, demonstrate promising results concerning CCMs and infantile capillary hemangiomas. 2,3 In our current communication, we postulate that oral propranolol administration could provide a novel, alternative approach for the treatment of adults and children with familial cavernous malformation cases of the central nervous system.…”
Section: Letter By Filippidis Et Al Regarding Article "Evaluating Stmentioning
confidence: 98%
“…The lesion demonstrated a significant shrinkage after 10 days of propranolol administration. 3 Promising data arise also from the management of cutaneous or nasal capillary infantile hemangiomas with propranolol using the same dosage scheme. 2 Leute-Labreze et al 2 observed the inhibition of growth of capillary infantile hemangiomas, approaching the total remission target by administering 2 to 3 mg propranolol per day by mouth divided into 2 to 3 doses after appropriate cardiology consultation without any side effects or any associated morbidity and mortality.…”
Section: Letter By Filippidis Et Al Regarding Article "Evaluating Stmentioning
confidence: 99%